Delayed Achievement of Oral Feedings Is Associated with Adverse Neurodevelopmental Outcomes at 18 to 26 Months Follow-up in Preterm Infants - Lainwala, Shabnam; Kosyakova, Natalia; Power, Kimberly; Hussain, Naveed; Moore, James E.; Hagadorn, James I.; Brownell, Elizabeth A. (American Journal of Perinatology, 2020)
Objective This study aimed to compare neurodevelopmental outcomes in preterm infants at 18 to 26 months corrected age (CA) who did versus did not achieve full oral feedings at 40 weeks postmenstrual age (PMA).Study Design This retrospective study included infants born between 2010 and 2015 with gestational age <32 weeks and followed between 18 and 26 months CA. Achievement of full oral feedings was defined as oral intake >130 mL/kg/d for >72 hours by 40 weeks PMA. Incidence of cognitive, language, or motor delay, or cerebral palsy at 18 to 26 months CA was compared in multivariable analyses for infants in the two feeding groups.Results Of 372 included infants, those achieving full oral feedings had lower incidence of any adverse neurodevelopmental outcome (p < 0.001) compared with those who did not achieve full oral feedings. In multivariable analyses, achievement of full oral feedings by 40 weeks PMA was associated with decreased odds of cognitive, language, and motor delays, cerebral palsy, and any adverse neurodevelopmental outcome at follow-up.Conclusion Achievement of full oral feedings by 40 weeks PMA was associated with better adjusted neurodevelopmental outcomes at 18 to 26 months CA. Inability to fully feed orally at 40 weeks PMA may be a simple, clinically useful marker for risk of adverse neurodevelopmental outcomes.
Keywords: preterm; neurodevelopmental outcomes; oral feedings; neonatal follow-up